A single-center retrospective study comparing safety and efficacy of endoscopic biliary stenting only vs. EBS plus nasobiliary drain for obstructive jaundice - Liu, Huan; Shi, Chuanke; Yan, Zhideng; Luo, Ming (Frontiers in Medicine, 2022)
Purpose Bile drainage is an important modality for extrahepatic obstructive jaundice, whether it is palliative or resectable patients. Currently, endoscopic bile duct drainage is preferred in clinical practice, including ENBD and EBS, both of which are commonly used due to their own advantages and disadvantages. The purpose of this study was to investigate the safety and efficacy of ENBD combined with EBS for obstructive jaundice. Methods We consecutively reviewed patients who underwent endoscopic biliary drainage in our institution from November 2014 to March 2021. All eligible patients were divided into the internal-external drainage group and the internal drainage group. Liver function, postoperative adverse events and the stent patency time were compared between the two groups. Results In 271 patients, a total of 356 times endoscopic biliary drainage were performed. All eligible patients were divided into the internal-external drainage group (n=74) and the internal drainage group (n=271). The internal-external drainage group was superior to the internal drainage group in terms of hospital stay (12.7±5.2 vs. 14.5±7.9 days, P=0.020) and stent patency time (8.1±3.9 vs. 4.3±2.7 months, P=0.001), which was in the liver Functional improvement and postoperative adverse events are also advantages. Conclusion Endoscopic internal-external bile duct drainage is an effective and safe modality for obstructive jaundice.